The Role of Nutrition in the Prevention and Intervention of Type 2 Diabetes - Guo, Yajie; Huang, Zihua; Sang, Dan; Gao, Qiong; Li, Qingjiao (Frontiers in Bioengineering and Biotechnology, 2020)
Type 2 diabetes (T2D) is rapidly growing epidemics, which lead to increased mortality rates and health-care costs. Nutrients (namely, carbohydrates, fat, protein, mineral substances and vitamin) sensing and management is central to metabolic homeostasis, therefore presents a leading factor contributing to T2D. Understanding the comprehensive effects and the underlying mechanisms of nutrition in regulating glucose metabolism and the interactions of diet with genetics, epigenetics and gut microbiota is helpful for developing new strategies to prevent and treat T2D. In this review, we discuss different mechanistic pathways contributing to T2D, and then summarize the current researches concerning associations between different nutrients intake and glucose homeostasis. We also explore the possible relationship between nutrients and genetic background, epigenetics and metagenomics in terms of the susceptibility and treatment of T2D. For the specificity of individual, precision nutrition depend on person’s genotype and microbiota is vital to the prevention and intervention of T2D.